Penyuluhan Konflik Lahan dan Deteksi Dini Gesekan Sosial di Wilayah Hukum Polda Jambi: Wilayah Polres Tanjung Jabung Timur - Prisgunanto, Ilham; Hamid, Supardi (Jurnal Pengabdian Kepada Masyarakat Kalam, 2023)
Land disputes are a complicated problem in legal handling to provide a sense of justice to the community. Land disputes conflict between communities and agribusiness companies, communities and local governments and even between communities themselves. There are still very few resolutions of land disputes that approach the restorative justice process, all through trial and judicial processes which require a lot of money, time and energy. The counseling provided by STIK PTIK will provide new knowledge about resolving land disputes outside of court. This counseling is aimed at investigators and law enforcement, namely East Tanjung Jabung police staff. That's not all, counseling is given to local governments and related agencies regarding land dispute resolution cases. The counseling was enthusiastically welcomed by the participants with a breakthrough in law enforcement with a win-win solution orientation by mediating and negotiating the resolution. The local genius approach makes community participation very important in this case.